Singing, health and wellbeing in young children - Welch, Graham Frederick; Baxter, Hazel (Frontiers in Psychology, 2025)
This exploratory, pre-post study considers the impact of collective singing within inner London Primary classrooms on young children’s vocal development and sense of health and wellbeing. Data on singing and wellbeing were collected from children between the ages of five and seven before and at the conclusion of a whole class singing program. The program was led by professional singers from a charitable singing foundation who visited the school every 2 weeks over a period of 6 months (January 2024 to June 2024). Class teachers were expected to lead collective singing with their classes between the visits and the program concluded with performance in central London. Singing development was measured using the Singing Voice Development Measure (SVDM) and a revised model of vocal pitch-matching development (VPDM). Children’s perception of their health and wellbeing was assessed through the Very Short Wellbeing Questionnaire for Children (VSWQ-C), the PANAS-C measure of emotional wellbeing (modified for younger children) and focus groups at the end of the program. Results suggest that there was a significant improvement in children’s singing competency and that their perceptions of health and wellbeing were sustained across the period. However, there was no clear evidence statistically of a significant relationship between singing, health and wellbeing, primarily because, although their singing competency improved, these young children were very positive on the health and wellbeing measures throughout the focus period. Nevertheless, children in focus groups reported being very positive about the singing program and its positive impact on their health and wellbeing.